(untitled) (Annals of Medical Research, 2021)
Aim: To compare the glutathione s-transferase α-4 (GSTA4) isoenzymes expression values in patients with lumbar spinal canal stenosis (LSCS) due to ligamentum flavum (LF) hypertrophy with patients no evidence of LF hypertrophy.Material and Methods: 27 LF specimens were obtained from patients with LSCS and 27 LF specimens were obtained from patients with lumbar discal hernia (LDH). Firstly these LF samples were analyzed histologically to identify the fibrosis and elastin degradation values. Then GSTA4 isoenzyme values were measured and compared.Results: The mean LF thickness was significantly higher in the LSCS group than in the LDH group (6.72±0.86 and 3.1±0.7 mm, respectively, p 0.005). Average elastin degradation degree was significantly higher in the LSCS group than LDH group (4.4 ±0.50 vs. 0.18±0.1, respectively, p 0.001). And avarage fibrosis degree was significantly higher in the LSCS group than LDH group (4.41±0.17 vs. 0.96±0.11, respectively, p 0.001). And significantly higherexpression of GSTA4 izoenzyme was observed in the LF samples obtained from patients with LSCS compared with controls (144.1±11.16 vs 51.75±21.53, respectively, p=0.009). Conclusion: Our findings in this study suggest that there is a relationship between LF hypertrophy and GSTA4 isoenzyme expression.